Evaluation Needs of Planting Water Using Cropwat Software at Darung Secondary Channel in Prawiro Kepolo Irrigation Area, Indramayu District - Mangambit Juliandar Simanjuntak; Mahdika Putra Nanda (Universitas Tribhuwana Tunggadewi Malang, 2025)
This study evaluates the availability and water needs in the Darung Secondary Channel (MG1-MG7) in the Prawiro Kepolo Irrigation Area, Indramayu District, during the second planting season. The water availability at the Darung Secondary Channel (DR) intake was calculated using the F.J. Mock method. In contrast, the water requirement in seven plots of mangosteen channel (MG1-MG7) was calculated by Cropwat simulation. Semi-monthly discharge data for 12 years is analyzed to determine the flagship discharge. The F.J. Mock method calculation results are 0.28 m³/second, and the field network data is 1.55 m³/second. So, the total availability of DR intake is 1.83 m³/second. The results of the Cropwat simulation show that the maximum water requirement in MG1-MG7 is 2.01 m³/second, resulting in a deficit of 0.18 m³/second. These findings confirm the need to optimize water in the deficit mangosteen channel. Recommendations include modernizing irrigation infrastructure and applying precision irrigation technology based on plants' needs. These measures are expected to improve water use efficiency and support agricultural productivity sustainability in the study area.